Utilization of Beauveria Bassiana Bals. -Criv. Fungus to Control Coffee Berry Borer (Hypothenemus Hampei F.) Invitro - Syahfitri, Windi Ely; Warsito, Kabul; Setiawan, Andi (ITScience (Information Technology and Science), 2025)
Coffee (Coffea sp) is one of the most important plantation commodities in Indonesia, largely due to its considerable economic value. However, coffee production faces significant challenges from pests such as the coffee berry borer (PBKo) (Hypothenemus hampei F), which can cause severe damage to crops, with losses reaching up to 100%. Biological control agents, particularly the entomopathogenic fungus Beauveria bassiana, have gained increasing attention as environmentally friendly alternatives to chemical pesticides. While the efficacy of B. bassiana against H. hampei has been widely documented, most previous studies have primarily targeted the adult or larval stages, often overlooking the differences in susceptibility among the various metamorphosis phases. This study addresses this research gap by systematically evaluating the effectiveness of B. bassiana as a biological control agent against PBKo across each stage of the pest’s metamorphosis-egg, larva, pupa, and imago-under in vitro conditions. Using a controlled experimental design, we assessed mortality rates in each developmental phase after exposure to B. bassiana treatment. The findings of this study are expected to provide comprehensive insights into the phase-specific efficacy of B. bassiana, identifying which metamorphic stage is most vulnerable to fungal infection. This knowledge is anticipated to improve biological control strategies, ultimately supporting more targeted and sustainable integrated pest management practices for coffee plantations. These advancements can enhance coffee yields and quality while reducing reliance on synthetic chemical pesticides.